TRIZ and AHP in early design stage of a Novel Reconfigurable Wheelchair / Sumit Desai...[et al.] - Desai*,, Sumit; Mantha,, Shankar; Phalle, Vikas (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
The Reconfigurable wheelchair incorporated with sit-to-stand and sit-to-sleep capabilities is the technological solution for extensive wheelchair users to promote their quality of life (QoL), safety and comfort. This paper presents the conceptual design of a reconfigurable wheelchair using the TRIZ and AHP integrated approach. The objective of this study was to develop optimal conceptual designs of a reconfigurable wheelchair by overcoming identified design conflicts. The TRIZ contradiction toolkit was employed in the early conceptual design phase. Based on the TRIZ inventive principles and developed design strategy, new reconfigurable wheelchair mechanism was modelled in SolidWorks environment, using a top-down modelling approach. Dimensions of a wheelchair were kept within the dimensions of a standard wheelchair. The newly modelled mechanism was refined using motion simulation capabilities of the SolidWorks software. The new mechanism was further integrated with different wheelchair design features by means of the morphological chart in order to get innovative conceptual designs. Further, Analytical Hierarchy Process (AHP) was utilized as a multi-criteria decision making technique for optimal conceptual design selection. Conceptual design-I (joystick controller with electric drive) received highest weight among all conceptual designs, hence selected as the optimal conceptual design. Consistency ratio (CR) for the pair-wise comparisons made throughout the AHP method was found less than 0.10. All AHP calculations were supported by Microsoft Excel Add-in for multi-criteria decision problems. For the purpose of functionality testing of newly modelled wheelchair, 3D printed wheelchair parts have been fabricated (using ABS material) and tested for desired mechanical movements. The methodology implemented in the present work can be utilized for upcoming applications in design of new assistive devices.